2017
DOI: 10.1159/000480349
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Protein Kinase C in Bipolar Disorder: A Review of the Current Literature

Abstract: Bipolar disorder (BD) is a major health problem. It causes significant morbidity and imposes a burden on the society. Available treatments help a substantial proportion of patients but are not beneficial for an estimated 40-50%. Thus, there is a great need to further our understanding the pathophysiology of BD to identify new therapeutic avenues. The preponderance of evidence pointed towards a role of protein kinase C (PKC) in BD. We reviewed the literature pertinent to the role of PKC in BD. We present recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 175 publications
(217 reference statements)
4
81
0
1
Order By: Relevance
“…The mice that took longer to re-entrain normal sleepwake rhythms after circadian disruption also displayed greater quinpirole-induced hyperactivity, indicative of a more mania-like state, however depressive-like behavior (forced swim test) was not affected 137,138 . Based on these studies and human clinical data, the pathophysiology of environmental circadian disruption underlying bipolar mania may be via altered protein kinase c activity affecting neuronal signaling in frontal and limbic brain regions 139 .…”
Section: Circadian Rhythm Disruption and Bipolar Disordermentioning
confidence: 99%
“…The mice that took longer to re-entrain normal sleepwake rhythms after circadian disruption also displayed greater quinpirole-induced hyperactivity, indicative of a more mania-like state, however depressive-like behavior (forced swim test) was not affected 137,138 . Based on these studies and human clinical data, the pathophysiology of environmental circadian disruption underlying bipolar mania may be via altered protein kinase c activity affecting neuronal signaling in frontal and limbic brain regions 139 .…”
Section: Circadian Rhythm Disruption and Bipolar Disordermentioning
confidence: 99%
“…This association is further supported by the role of DAG in bipolar disorder-associated signalling. In mammalian models, DGK competes with PKC for binding to DAG, thereby regulating PKC activity, and dysregulation of the PKC signalling pathway has been widely demonstrated in bipolar disorder patient populations and following therapeutic treatment ( Sakai and Sakane, 2012 ; Saxena et al, 2017 ). Numerous studies have identified upregulated PKC activity in bipolar disorder patients ( Friedman et al, 1993 ; Wang and Friedman, 1996 ), with this activity being reduced by both lithium ( Friedman et al, 1993 ; Wang and Friedman, 1989 ) and VPA ( Ramadan et al, 2011 ; Watson et al, 1998 ) in animal models and patient studies ( Katsel et al, 2008 ; Soares and Mallinger, 1997 ; Wang et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinase C (PKC) has often been suggested as playing a key role in BD, as both lithium and valproate inhibit PKC signaling [88]. Thus, inhibitors of PKC have been considered as potential therapeutic agents [89].…”
Section: Discussionmentioning
confidence: 99%